Assessment of diesel engine performance using spirulina microalgae biodiesel. (1st January 2019) - Rajak, Upendra; Nashine, Prerana; Verma, Tikendra Nath
Abstract: The present work encompasses combustion, performance, and emission parameters of experimental investigations of a single cylinder, four stroke, water cooled, direct injection (DI), naturally aspirated compression ignition (CI) engine with a rated power output of 3.7 kW at constant engine speed (1500 rpm) using diesel and different blends of microalgae spirulina . The microalgae spirulina blend of ratio with diesel (BYY) where YY indicates blending percentage (0%, 20%, 40%, 60%, 80%, and 100% volume basis with diesel respectively) with different engine loading condition (25%, 50%, 75% and 100%) were compared with diesel at CR17.5:1. The output illustrates that the most optimum value is B20% when compared with diesel. The result depicts firstly that there is a reduction in brake thermal efficiency by 0.98%, exhaust gas temperature by 1.7%, hydrocarbon (HC) by 16.3%, carbon monoxide (CO) by 3.6%, NOX emission by of 6.8%, and smoke emission by 12.35% respectively. Secondly, there is an increase in specific fuel consumption by up to 5.2% and CO2 emission by 2.8% for spirulina blend ratio (B20%) as compared to diesel (B0%) at full load condition engine with constant engine speed. Highlights: Diesel-biodiesel blends obtained better performance of B20 as compared to diesel. Microalgae spirulina biodiesel combustion performance is comparable with diesel. Blends were found as an effective way to reduce the NOX and PM emissions. Shows the enormous potential to reduce of CO2 emission with increase engine load.